Interleukin‐34 promotes tumor progression and metastatic process in osteosarcoma through induction of angiogenesis and macrophage recruitment. Issue 1 (13th December 2014) - Ségaliny, Aude I.; Mohamadi, Amel; Dizier, Blandine; Lokajczyk, Anna; Brion, Régis; Lanel, Rachel; Amiaud, Jérôme; Charrier, Céline; Boisson‐Vidal, Catherine; Heymann, Dominique
Abstract : Interleukin‐34 (IL‐34) was recently characterized as the M‐CSF "twin" cytokine, regulating the proliferation/differentiation/survival of myeloid cells. The implication of M‐CSF in oncology was initially suspected by the reduced metastatic dissemination in knock‐out mice, due to angiogenesis impairment. Based on this observation, our work studied the involvement of IL‐34 in the pathogenesis of osteosarcoma. The in vivo effects of IL‐34 were assessed on tissue vasculature and macrophage infiltration in a murine preclinical model based on a paratibial inoculation of human osteosarcoma cells overexpressing or not IL‐34 or M‐CSF. In vitro investigations using endothelial cell precursors and mature HUVEC cells were performed to analyse the involvement of IL‐34 in angiogenesis and myeloid cell adhesion. The data revealed that IL‐34 overexpression was associated with the progression of osteosarcoma (tumor growth, lung metastases) and an increase of neo‐angiogenesis. In vitro analyses demonstrated that IL‐34 stimulated endothelial cell proliferation and vascular cord formation. Pre‐treatment of endothelial cells by chondroitinases/heparinases reduced the formation of vascular tubes and abolished the associated cell signalling. In addition, IL‐34 increased the in vivo recruitment of M2 tumor‐associated macrophages into the tumor tissue. IL‐34 increased in vitro monocyte/CD34 + cell adhesion to activated HUVEC monolayers under physiological shear stress conditions. This work also demonstrates that IL‐34 is expressed by osteosarcoma cells, is regulated by TNF‐α, IL‐1β, and contributes to osteosarcoma growth by increasing the neo‐angiogenesis and the recruitment of M2 macrophages. By promoting new vessel formation and extravasation of immune cells, IL‐34 may play a key role in tumor development and inflammatory diseases. Abstract : What's new? The newly discovered cytokine IL‐34 shares a common receptor with macrophage‐colony stimulating factor (M‐CSF) and is involved in the regulation of myeloid cell growth, differentiation, and survival. The present study suggests that it may have a role in osteosarcoma. In vitro and in vivo experiments indicate that IL‐34 expression is regulated by TNF‐α and IL‐1β and that its overexpression is associated with an increase in osteosarcoma growth and metastasis. IL‐34 was further found to be pro‐angiogenic and to promote M2 macrophage recruitment into tumors.